Educação integral em tempo integral na Amazônia: um diálogo com os profissionais de uma escola pública em Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
At the centre of the discussions that permeate the school universe, the policy of working hours has been redefining several pedagogical practices and introducing social changes of restructuring in the role of the school and its professionals. Given this, the study investigates the role of school professionals in articulation with the understanding and perception of the policy that induces the extension of the journey. In this context, we ask ourselves: How do school professionals understand and resignify their work in view of the implementation of the full-time inductive education policy? To understand the professional importance of all school members in the face of this new educational context and its construction, authors such as Moll (2010), Cavaliere (2010), Gadotti (2009), Paro (2009) were defined as theoretical support. , among others. Regarding the theme that involves the Pedagogical Political Project we seek support in the studies of Veiga (1998), Vasconcelos (2000), Gandin (2001), Sarturi (2016). The research is qualitative in nature, being the approach outlined by the Case Study, which seeks to understand the role of school professionals, the understanding of the Pedagogical Political Project and the changes implemented by the More Education (Mais Educação) and New More Education (Novo mais Educação) Programmes, inducing the expansion of school day. The techniques of data collection used were the interview, document analysis, observation with records in the observation diary that contain descriptive reports of the school routine and its subjects (manager, teachers and program monitors). The “locus” of investigation was the Sister Leodgard Gausepohl Municipal Elementary School, located in the urban area of Santarém-Pará. For the data analysis, it was taken as subsidy Bardin (2011), with the content analysis through the following dimensions: a) Subjective / Personal Dimensions, b) Institutional / Organizational, c) Instructional / Relational and d) Sociopolitical. The results contributed to demonstrate how professionals gave a new meaning to their work from the moment they perceived themselves as part of related relationships between reality and their practices in daily school life. These evidences were demonstrated when understanding the relationships with the study dimensions, in which they reflect disruption of old practices and implementation of transformative actions of the educational space and, above all, highlight possibilities in the construction of an Integral Education in the Amazon.
Keywords: Educação Integral; Escolas de Tempo Integral; Profissionais da Educação; Amazônia; HISTÓRIA, POLÍTICA E GESTÃO EDUCACIONAL NA AMAZÔNIA; EDUCAÇÃO